Structural evolution of the Hudsonian Torngat Orogen in the North River map area, Labrador: Evidence for east-west transpressive collision of Nain and Rae continental blocks - Van Kranendonk, Martin; Ermanovics, Ingo (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1990)
Summary The Hudsonian Torngat Orogen In the North River map area, Labrador, evolved through: (1) early thrusting and associated isoclinal folding in lower Proterozoic supra crustal cover rocks, and the development of a regional tectonic fabric at peak metamorphic grade; (2) folding and intense shearing on subvertical planes, characterized by a sub-horizontal NNW-plunging extension llneation during sinistral transpression; and (3)Å-directed thrusting during uplift of the orogen. These structures are Interpreted as progressive features that resulted from E-Woblique collision of the Archean Nain and Rae continental blocks across a 160°-striking boundary.